Discharge and annulment from bankruptcy its procedure and effects / Hanizan Mohamed Inzan - Mohamed Inzan, Hanizan (Faculty of Law, 1982)
Once a debtor becomes insolvent and is unable to pay his debt when they are due because of the lack of cash or his deliberate refusal to pay the creditors either the debtor or the creditors can make a petition for the court to take over the administration of the debtor's estate and its distribution among creditors. The bankruptcy petition can be presented once the debtor has committed an act of bankruptcy under s.3(3) and s.5(1) of the Bankruptcy Act 1965. On the petition being recieved by the court the court will then make a recieving order together with the Adjudication Order under s.24(1). It is at this juncture that the Official Assignee's office will be instructed by the court to act on behalf of the bankrupt. After undergoing the public examination and being adjudicated a bankrupt the bankrupt can under s.33 of the Bankruptcy Act apply for a discharge. But if the bankrupt can prove that he has paid his debts in full and ought not to have been adjudged a bankrupt then the bankrupt can apply for an annulment of the Adjudication Order. The effect of the order of discharge is laid down in s.35 of the Bankruptcy Act. Once discharged a bankrupt's liability to the other creditors will be released but not those of the Government of the Federation and The States unless released by the Prime Minister and the Head of State respectively.